Framing analysis on Luwuk Post on the news of regional head election campaign (Pilkada) Banggai Regency in 2020 - ridha risma yunita, Ridha Risma Yunita; suanti tunggala, Suanti Tunggala; ken amasita, Ken Amasita Saasdjad (Universitas Ahmad Dahlan, 2022)
This research aims to find out the framing and construction of Luwuk Post media reality to the news of the 2020 Banggai Regency regional head election. To collect data is done by identifying the overall news document published in the Daily Luwuk Post newspaper during the campaign period based on PKPU No. 13 of 2020 which began from November 22, 2020 to December 5, 2020. The research method used in this research is to use a qualitative descriptive approach. The data sources used in this study are primary data and secondary data. In this study, the data analysis technique used is an analysis tool using Nvivo, Nvivo as an analysis tool that displays data in the form of text and images through the process of coding data. The sample in this study is textually the title of the news of campaign activities in Banggai Regency in the 2020 Election in The Luwuk Post Newspaper Daily period of November 22, 2020 to December 5, 2020 into a sample of research. With the results of the study that the framing of Luwuk Post media on the news of the 2020 Banggai District Regional Election Campaign with the highest percentage consisted of Define problems with a news point of view of 66%, Diagnose Causes with 75% news issues, make moral judgment with a positive frame of 76%, and the last Treatment recommendation with 88% source suggestions. Data coding results through NVIVO 12 Plus show the candidate pair H. Herwin Yatim – H. Mustar Labolo (WINSTAR) packages his interests by making the agenda of government or government policy as the object of news and efforts to influence the lives of readers in the sense of making choices to WINSTAR candidate pairs.